AB1150 ECONOMIC IMPACT ASSOCIATED TO BIOLOGICAL THERAPY / SYNTHETIC FAME OPTIMIZATION IN A COHORT OF PATIENTS WITH CHRONIC INFLAMMATORY RHEUMATIC DISEASES TREATED BY OBJECTIVES. (2nd June 2020) - Castro, P.; Onteniente, A.
Abstract : Background: Therapeutic decision-making for biologic-therapies/ synthetic FAME (BT/SD) dose optimization, should be based on optimal disease activity results according to a treatment strategy by objectives. The goal of BT optimization is to guarantee long-term effectiveness and safety, maximising economic savings Objectives: To evaluate BT optimization patterns in patients with rheumatic diseases (RD) and associated economic savings. Methods: An observational and prospective study, which included a cohort of patients with rheumatoid arthritis (RA), spondyloarthropathies (SA) and psoriatic arthritis (PsA) treated with BT from January 2014 to December 2019. BT optimization, achieved by reducing or prolonging the interval at least one dose, was indicated when patients have more than 6 months of treatment and are in clinical remission (DAS28 <2.6 for RA and PsA, and BASDAI<2 for SA) or minimal clinical activity (DAS28<3.2 for RA and PsA, and BASDAI<4 for SA). Variables were described as frequencies and means. Diagnosis, BT (abatacept, adalimumab, apremilast, baricitinib, certolizumab, etanercept, golimumab, ixekizumab, secukinumab, tocilizumab, tofacitinib, and ustekinumab), dose regimens, total treatment duration, time on BT optimization (TO) and treatment costs were collected. Cost savings were calculated per patient by comparing optimization treatment costs to conventional treatment and globally by comparing real cost to theoretical conventional doses cost. Results: A total of 260 patients were included in the study. Switching were observed in 32.7%. From all patients, 53% were candidates for BT optimization (according to diagnosis: 60.9% with RA, followed by 52.2% with SA and 43.4% with PsA) A 40% of patients with BT optimization were treated with adalimumab and etanercept being also the most common BT used in RD treatment BT optimization allowed a pharmaceutical saving of € 177, 539.40 per year against the use of conventional therapy, resulting in a reduction of the total cost of €1, 065, 236.40 in the last 6 years. The saving per patient / year was € 707.63 for RA; € 850, 40 for SA and of €493, 21 for the PsA. Conclusion: Therapeutic decision-making based on validated disease activity scales has allowed the BT optimization in approximately 53% of patients with RD. BT optimization allowed a pharmaceutical saving of € 177, 539.40 per year being higher in the SA (€ 850.40) followed by the RA (€ 707.63) and finally the PsA (€ 493.21) The BT optimization allows to reduce costs maintaining the effectiveness and safety. Disclosure of Interests: None declared